Let's dust off development tracks for Europe: democracy and civilisation - Kiełczewski, Stanisław (Odświeżmy tropy rozwojowe Europy: demokrację i cywilizację, 2011)
EU strategies ought to be built with respect for the idea of a democratic society, which is one of the most valuable accomplishments of our Western civilization and united Europe. Democracy, which so often in the course of history has been threatened, effectively limited, and at times overthrown by different strains of totalitarianism and anarchy, has always required particular care from a society conscious of its values so that it may fulfil the expectations that it generates and not become a fig leaf for the misuse of power and manipulation of society. At present, the EU lacks a vision of its mission as well as strategy – the pursued goals are technical, integration without solidarity is doubtful and shared interests are rather seeming and shallow
Ekonomia = Economics, 2011, Nr 2 (14), s. 26-31
Keywords: real and formal democracy; development goal; development condition; strategy; offensive strategy